Teachers' perceptions of behavioural problems manifested by Grade 11 and 12 learners in three Namibian schools - Akawa, Ester Anna Nelago (Rhodes University, Faculty of Education, Department of Education, 2014)
In Namibia today few learners with behavioural and learning problems are within special schools as most are placed within the mainstream school system. Placing these learners within the mainstream system is part of the policy of Inclusive Education (IE) because it argues that this would benefit these learners and also save resources. IE is concerned with addressing barriers to learning and behavioural problems are regarded as one of these barriers. IE argues for a series of new approaches to the diagnosis and response to learners with behavioural problems. This poses challenges for teachers in mainstream schools. Teachers are at the forefront of this situation as they are usually the first to observe and experience the behavioural problems in the schools and are expected to respond appropriately. They find this situation both challenging and problematic. This research explores a sample of teachers' perceptions of learners' behavioural problems. To collect in-depth information, this study followed a qualitative approach with a case study design. The data were collected through semi-structured interviews, supplemented with observation and document analysis. The study consisted of fifteen respondents: three principals, three teacher counsellors and nine teachers from the three selected schools. This study illuminates the types of behaviour that teachers encounter, the impact of these behaviours, the factors seen as contributing to these behaviours, and how teachers and the school system deal with these behaviours. In addition the study applies Bronfenbrenner's bioecological model (1992) to explain how the behaviours manifested by Grade 11 and 12 learners, and identified as problematic by teachers, are part of an interconnected nested social system. The results from the study indicate the manifestation of behavioural problems to be common occurrences in secondary schools are evident, amongst others, through fighting, bullying, substance abuse, truancy, and disrespect of teachers and authority. The teachers pointed to the prevalence of these problems as well as the serious impact such problems have on these learners, their fellow learners, and on the teachers. The teachers identified a complex array of what they saw as contributing factors located within the school, peer groups, family and home circumstances, the local community, as well within the national education policy, the economy and society. The study points to some specific, as well as broader, lessons and opportunities for action both for those managing the education system at the national level and for schools and teachers.
Keywords: Education, Secondary -- Namibia; School children -- Namibia -- Attitudes; Learning disabilities -- Social aspects; Behavior disorders in children -- Education (Secondary) -- Namibia; Children with social disabilities -- Education (Secondary) -- Namibia; Emotional problems of children -- Education (Secondary) -- Namibia; Teachers -- Job stress -- Namibia